Nonylphenol Removal from Water and Wastewater with Alginate-Activated Carbon Beads - Angelica A. Chacon; Elizabeth Noriega Landa; Sheng Yin; Ahsan Habib; Kiana L. Holbrook; Luis R. Duran Bojorquez; Sabur Badmos; Dino Villagrán; Wen-Yee Lee (Separations)
In this study, eco-friendly and sustainable alginate-activated carbon (Alg-C)-based beads were synthesized and characterized for the adsorption of nonylphenols (NPs) from aqueous environments under various conditions. The surface characterization, functional groups, and adsorption behavior were analyzed using multiple analytical techniques. The effect of key parameters, including dosage, pH, temperature, and reusability, were evaluated. Isotherm and kinetic studies revealed that the adsorption process followed a pseudo-second-order kinetic model and aligned with the Freundlich isotherm, indicating a heterogeneous surface. The beads exhibited a high removal efficiency of 97% over five reuse cycles in a 50 mL solution of 10 mg L−1 NPs under static conditions, demonstrating their recyclability. Thermodynamic analysis suggested potential electrostatic interactions, supported by positive Gibbs free energy values. The highest removal performance was achieved within 90 min, with adsorption capacities from 0.10 to 0.39 mg g−1. Additionally, the performance of Alg-C beads remained stable across different pH levels, highlighting their robustness. When tested with wastewater samples, Alg-C beads maintained high removal efficiency, with no significant matrix effects observed. These results underscore Alg-C beads as a promising and sustainable solution for the elimination of NPs from contaminated water sources.